Does purchasing power parity hold in OECD countries? - (:unkn) unknown (My University, 2010)
In this study, the aim is to analyse the validity of Purchasing Power parity (PPP) for the OECD countries. For this aim, the real exchange rates are examined using the different unit root tests which are The Augmented Dickey Fuller Test (ADF; 1979, 1981), The Phillips Perron Test (PP, 1988), The Kwiatkowski, Phillips, Schmidt and Shin Test (KPSS, 1992), and also the results of these tests are compared. The test results show some evidence that stationary real exchange rate series can be taken as evidence supporting the validity of PPP. Most studies have used the common unit root methodology such as ADF and PP to test PPP. To get rid of the lack of success of the common unit root tests, we use KPSS Test which is believed to be more efficient and have higher power than ADF and the PP Tests.The results of KPSS test provide some evidence in favor of PPP for the most of the OECD countries, while ADF and PP tests failed to find evidence of PPP in the great majority of the OECD countries. © EuroJournals Publishing, Inc. 2010.
Keywords: Purchasing power parity; Real exchange rate; Unit root test